2011
DOI: 10.1111/j.1365-2834.2011.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress, job satisfaction and job performance among hospital nurses in Kampala, Uganda

Abstract: On-the-job training for nurse managers in human resource management to increase understanding and advocacy for organizational support policies was recommended. Research to identify organizational, family or social factors which contribute to reduction of perceived occupational stress and increase job satisfaction and job performance was recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
153
4
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(174 citation statements)
references
References 24 publications
11
153
4
6
Order By: Relevance
“…For example, the capability of employees to properly manage their PHS and PSS in executing job may lead to an enhanced JOP in organizations [9][17] [18]. Although the nature of this relationship is interesting, the role of occupational stress as an important antecedent is inadequately explained in the workplace stress models [19] [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the capability of employees to properly manage their PHS and PSS in executing job may lead to an enhanced JOP in organizations [9][17] [18]. Although the nature of this relationship is interesting, the role of occupational stress as an important antecedent is inadequately explained in the workplace stress models [19] [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, several recent studies using a direct effect model were conducted to investigate occupational stress based on different samples like 254 nurses over three nursing shifts [17], 333 nurses from four hospitals in Kampala, Uganda [18], 304 call center employees in the UK [19], 100 nurses from a large general teaching hospital in Scotland [21], and 213 employees at six geographic Logistics Centers within a medium-sized Fortune 500 company in the Southeastern 3rd International Conference on Information, Business and Education Technology (ICIBET 2014) United States [24]. The outcomes of these studies reported that the inability of employees to manage, regulate and control their job had invoked employees' physiological and psychological stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Personal characteristics; attitudes and behaviors are factors that influence nurse job satisfaction. 8 Another study related to the Information on levels of job satisfaction, the intrinsic and extrinsic job factors are also essential for health care managers who are committed to the happiness and satisfaction of their employees, and to quality of patient care. Respondents were also somewhat more dissatisfied with extrinsic work factors (58%) than with intrinsic factors (52, 5%).…”
Section: Discussion:-mentioning
confidence: 99%
“…Community satisfaction may not be achieved if the government apparatus as a service provider is not satified in the work [1] [2] . Job satisfaction can be obtained by gaining praise for the work, placement, treatment, equipment, and a good working environment atmosphere.…”
Section: Introductionmentioning
confidence: 99%